Information Disclosure and Corporate Governance - HERMALIN, BENJAMIN E.; WEISBACH, MICHAEL S. (Journal of Finance, 2012)
ABSTRACT Public policy discussions typically favor greater corporate disclosure as a way to reduce firms' agency problems. This argument is incomplete because it overlooks that better disclosure regimes can also aggravate agency problems and related costs, including executive compensation. Consequently, a point can exist beyond which additional disclosure decreases firm value. Holding all else equal, we further show that larger firms will adopt stricter disclosure rules than smaller firms and firms with better disclosure will employ more able management. We show that mandated increases in disclosure could, in part, explain recent increases in both CEO compensation and CEO turnover rates.